Peran Guru Pendidikan Agama Islam (PAI) Dalam Menguatkan Pondasi Keagamaan Siswa di Desa Empus Kecamatan Bahorok Kabupaten Langkat - Muhammad Solihin Pranoto (Yayasan Rahmat Islamiyah, 2023)
The purpose of study was determine the role of the PAI teacher in strengthening the religious foundations of students in Empus Village, Bahorok District Langkat Regency. The role PAI teachers in the teaching and learning process determines the final result of students. PAI teachers are not only required to teach but must be able to foster moral norms or the character of their students. PAI teachers are spritual father for students, who provide food and knowledge, moral development (noble character)and correct the bad behavior of their students. Therefore religious teachers have a high position in Islam. According to Al-Ghazali, the main task of the PAI teacher is to perfect, clean, purify and bring the human heart closer to Allah SWT. PAI teachers have roles that require them to guide their student know God (Akidah), Al-Qur’an along with the procedures for reading it, and Syari’at (Fiqh).